Conflict Management in Indonesia: Policy Perspective and Analysis - Sugit Arjon (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2018)
This article focuses to analyze the roots of violence and this article examines at case studies from Indonesia. This article also aims at answering the effectiveness of policy in the conflict management by analysing the critical factors that involved in violent conflicts and briefly seek alternative solution to prevent it to happen in the future. This article aims to answer two central questions, firstly, how effective the Indonesian government policy on security and conflict. Secondly, what are the roles of NGOs to support the effectiveness of the policy on security and conflict. To prevent the future conflicts, there are three effective strategies that can be implemented and it need the collaboration between the policymakers and society. First, to design an effective early warning mechanism which able to inform a potential friction that can escalate to bigger conflict. Second, an effective policy to prevent conflict, to manage conflict, and peace building mechanisms in post-conflict. Third, urge the participation of non-state actors in conflict management. The Indonesian government and house of representatives have passed the bill on social conflict management written as Law No. 7/2012 or known as UU PKS. However, UU PKS arguably leaves plenty of loopholes. Moreover, the activities of NGOs on the conflict management can be divided into two main categories: public engagement and advocacy. Public engagement activities focus on services to the public while on the advocacy focuses to maintain communication and put pressure to the government. In public engagement activities, the NGOs offer the service to provide psychological and legal assistance, consulting the victims rights, consulting, legal advice, psychosocial support to the victims. Moreover, in the advocacy approach, the NGOs maintain the discussion and lobby to the government to ensure the peace and justice in law enforcement.